2015
DOI: 10.1128/genomea.01036-15
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Kerstersia gyiorum CG1, Isolated from a Leg Ulcer

Abstract: We report the first draft genome sequence of Kerstersia gyiorum from a leg ulcer of a patient with diabetes and osteomyelitis. The 3.94-Mb genome assembly included 3,428 annotated coding sequences with an N50 of 223,310 bp and a plasmid encoding a type IV secretion system gene and two antitoxin genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Genome sequencing of K. gyiorum has been reported previously, 27 , 31 which laid the foundation for further research. In previous reports, smoking, drinking alcohol, obesity, and unhealthy residential environments were considered risk factors for infection.…”
Section: Discussionmentioning
confidence: 99%
“…Genome sequencing of K. gyiorum has been reported previously, 27 , 31 which laid the foundation for further research. In previous reports, smoking, drinking alcohol, obesity, and unhealthy residential environments were considered risk factors for infection.…”
Section: Discussionmentioning
confidence: 99%
“…K. gyiorum appears as a human pathogen described in the literature reviewed in nine occasions, being isolated from urine samples [9], ulcers [10,11] sputum [12] and causing chronic otitis in five cases [2][3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…Though a draft genome of K . gyiorum was announced by Greninger et al [15], a comprehensive genome analysis of this organism is still not available to date. For this study, we presented a complete genome sequence of recently identified isolate K .…”
Section: Introductionmentioning
confidence: 99%